Pengaruh Good Corporate Governance Terhadap Internet Financial Reporting - Auliffi Ermian Challen; Imelda Sari; Sheila Ariska; Syifa Nia Muslimah (Universitas Islam Islam Sumatera Utara, 2023)
The purpose of this study is to analyze how the influence of good corporate governance on disclosure of internet financial reporting (IFR). Good corporate governance in this study is proxied by the ownership structure (managerial ownership and public ownership), the characteristics of the board of commissioners (number of members of the board of commissioners and number of board meetings), and characteristics of the audit committee (number of members of the audit committee and number of audit committee meetings). The population in this study were all companies listed on the Indonesia Stock Exchange. Based on the purposive sampling method, the number of samples in this study were 392 companies. Testing the research hypothesis using multiple regression analysis. The test results show that the Â managerial ownership have a positive effect on disclosure of internet financial reporting. Meanwhile, the public ownership, the number of members of the board of commissioners, the number of board meetings, the number of members of the audit committee, and the number of audit committee meetings do not affect the disclosure of internet financial reporting.